Improving Students’ Reading Ability Through Reciprocal Teaching Method - Musdalifah Musdalifah; Nuril Firdaus; Fitriani Fitriani (JOEY: Journal of English Ibrahimy, 2023)
This study aims to determine the implementation of reciprocal teching method forimprovingthestudents reading ability at MTS Nurul Huda GondolBuleleng Bali. This is one of the method that can be applied by the teacher in teaching learning process. Through a reading ability that must be mastered by the students in learning English, it is important to be applied by the creative method while teaching learning process. This research conducts in Classroom Action Research (CAR) which consists of two cycles, each cycle included planning, implementing, observing, and reflecting. The cycle finishes when the indicators of success had achieved the completeness of learning set by the school. Completenessof learning for grade VIII subjects is 75%.The results show an increase of students' reading ability its learning outcomes in each cycle. The increase in learning outcomesshows in the pretest results with the percentage of completeness of learning 13,64% and there was an increase in the results of the post test cycle 1 to 40,91%, and an increase again in the results of the post test cycle 2 to 90,90 %. The increase in learning outcomes from the results of the pre-test , post-test cycle I to post-test cycle II was due to improvements in the reciprocal teaching method after evaluating the learning process activities and learning outcomes.From the results of observations in the learning process of students’ reading ability in the VIII grade of MTS Nurul Huda GondolBuleleng Bali, the students show a good response. Itconclude that learning using reciprocal teaching method.